PENGARUH FASILITAS PERPUSTAKAAN, TEMAN SEBAYA, DAN KOLEKSI BUKU TERHADAP MINAT BACA SISWA SMK TEUKU UMAR SEMARANG - Kirana Paramesti, Daiva; Oktarina, Nina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of library facilities, peers, and book collections on the reading interest of students majoring in Office Management and Business Services at SMK Teuku Umar Semarang. This study uses a quantitative method with a descriptive quantitative approach. The research population consisted of 96 students in grades X and XI, all of whom were sampled using saturated sampling techniques. Data were collected through a Likert scale questionnaire, while data analysis was performed using multiple linear regression analysis, including classical assumption tests, f-tests, t-tests, and determination coefficients. The results showed that library facilities, peers, and book collections simultaneously had a positive and significant effect on students' reading interest. However, partially, only the peer variable had a positive and significant effect and was the dominant factor in increasing students' interest in reading, while library facilities and book collections had a positive but insignificant effect. The coefficient of determination of 35.2% indicates that students' interest in reading is influenced by these three variables, while the remaining percentage is influenced by other factors outside this study. This study highlights the important role of students' social environment in developing reading interest and emphasizes the need for more innovative and student-oriented library management.